A STUDY ON IMPACT OF NEWSPAPER ADVERTISEMENT ON CONSUMER BEHAVIOUR IN KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The main aim of the study is to study the impact of Newspaper Advertisement on consumerbehaviour and identify the positive and negative influence of newspaper advertisements. Therelevant information for this research was gathered from both main and secondary resources.